The role of magnetic order in VOCl. (24th May 2019) - Ekholm, M; Schönleber, A; van Smaalen, S
Abstract: VOCl and other transition metal oxychlorides are candidate materials for next-generation rechargeable batteries. We have investigated the influence of the underlying magnetic order on the crystallographic and electronic structure by means of density functional theory. Our study shows that antiferromagnetic ordering explains the observed low-temperature monoclinic distortion of the lattice, which leads to a decreased distance between antiferromagnetically coupled V–V nearest neighbors. We also show that the existence of a local magnetic moment removes the previously suggested degeneracy of the occupied levels, in agreement with experiments. To describe the electronic structure, it turns out crucial to take the correct magnetic ordering into account, especially at elevated temperature.